2013
DOI: 10.1002/chem.201204005
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Oxidation of Sulfonamide Antibiotics: Aromatic Nucleophilic Substitution of an Aniline Radical Cation

Abstract: Sulfonamide antibiotics are an important class of organic micropollutants in the aquatic environment. For several, sulfur dioxide extrusion products have been previously reported upon photochemical or dark oxidation. Using quantum chemical modeling calculations and transient absorption spectroscopy, it is shown that single‐electron oxidation from sulfadiazine produces the corresponding aniline radical cation. Density functional theory calculations indicate that this intermediate can exist in four protonation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…It was reported that the para-position of aniliny radical cation of sulfadiazine could be subjected to intermolecular nucleophilic attack in which a pyrimidine nitrogen acted as a nucleophile [10,36]. This attack could lead to the intermolecular rearrangement (Smiles-type), resulting in SO 2 extrusion [10,36]. In the present study, the ␣-carbon adjacent to the sulfonamide group possessed strong positive charge in the resulting SMZ radical cation, which facilitated the nucleophilic attack of pyrimidine nitrogen.…”
Section: Reaction Products and Transformation Pathwaysmentioning
confidence: 68%
See 2 more Smart Citations
“…It was reported that the para-position of aniliny radical cation of sulfadiazine could be subjected to intermolecular nucleophilic attack in which a pyrimidine nitrogen acted as a nucleophile [10,36]. This attack could lead to the intermolecular rearrangement (Smiles-type), resulting in SO 2 extrusion [10,36]. In the present study, the ␣-carbon adjacent to the sulfonamide group possessed strong positive charge in the resulting SMZ radical cation, which facilitated the nucleophilic attack of pyrimidine nitrogen.…”
Section: Reaction Products and Transformation Pathwaysmentioning
confidence: 68%
“…4), and reaction between SO 4 • − and aniline could generate an aniliny radical cation [35]. Formation of aniliny radical cation has been confirmed by quantum chemical modeling calculation and transient absorption spectroscopy studies on single-electron oxidation of sulfonamides [36]. It was reported that the para-position of aniliny radical cation of sulfadiazine could be subjected to intermolecular nucleophilic attack in which a pyrimidine nitrogen acted as a nucleophile [10,36].…”
Section: Reaction Products and Transformation Pathwaysmentioning
confidence: 81%
See 1 more Smart Citation
“…The rate of degradation of the neutral species may outcompete the deprotonation, as supported by our higher degradation rates at lower pH. 49 Implications for the Environmental Applications of CSIA for SMX. In this study, we assessed for the first time the applicability of CSIA to monitor the biodegradation and photolysis of the antibiotic SMX.…”
Section: ■ Materials and Methodsmentioning
confidence: 91%
“…[49,50,11,51]; that choice was dictated by the fact that electron densities and optimum geometries of some of the investigated dyes exhibit a large dependence on the dielectric environment [30]. For the same reason we have not tested the SMD solvation model [48], a method designed to compute absolute solvation energies starting from gas-phase optimization/Hessian calculations, although there is evidence that SMD is capable of very accurate predictions of redox free energy for small molecules [9,10].…”
Section: Experimental Datamentioning
confidence: 96%